Determinants of Continuous Smartwatch Use and Data-Sharing Preferences With Physicians, Public Health Authorities, and Private Companies: Cross-Sectional Survey of Smartwatch Users - Anthony James Goodings; Kayode Philip Fadahunsi; Derjung M Tarn; Jennifer Lutomski; Allison Chhor; Frances Shiely; Patrick Henn; John O'Donoghue (Journal of Medical Internet Research)
Abstract BackgroundSmartwatches are widely adopted globally for tracking health metrics, offering potential for enhancing individual health care and public health efforts. Continuous use of the devices and users’ willingness to share the data collected are critical to realizing their full benefits. ObjectiveThis study aimed to identify key factors that determine continuous smartwatch use and users’ comfort levels in sharing health data with health care providers and public health authorities. MethodsA cross-sectional online survey of current and past smartwatch users (aged >18 years) was conducted to assess determinants of continuous use based on the Expectation-Confirmation Model (ECM) and user comfort levels with different data-sharing methods. Structural equation modeling was used to evaluate relationships between habit formation, satisfaction, perceived enjoyment, and perceived usefulness with continuous use. Wilcoxon signed-rank tests were used to analyze user comfort in sharing data, comparing noninternet- versus internet-based sharing methods and fully versus partially anonymized data. ResultsA total of 273 responses were analyzed, with participants aged 18‐65 (mean 35.6, SD 11.7) years. The results indicate that continuous use of smartwatches is explained by habit (βPβPβPβPβPβPPP ConclusionsHabit formation and satisfaction emerged as pivotal drivers of continuous intention to use smartwatches, emphasizing the need for features that foster integration into daily routine and a rewarding user experience. Preferences for noninternet-based data sharing with physicians highlight privacy concerns that must be addressed to build users’ trust. By aligning device features and data-sharing protocols with user preferences, manufacturers, health care providers, and policy makers can enhance user engagement and maximize the potential of smartwatches to support individual health management and public health initiatives.